The effectiveness of Customer Relationship Management (CRM) systems in improving optical customer satisfaction: A meta-analysis and bibliometric study (Jakarta Region) - Kusumo, Sri Wahyu Budoyo; Wibowo, Arraywed Yudita; Wicaksono, Ardhitya Furqon; Antono, Judi; Nuvida, Levya Otivian (Privietlab, 2026)
The rapid advancement of digitalization in the retail sector has compelled optical businesses to adopt Customer Relationship Management (CRM) systems to enhance customer loyalty, service personalization, and operational efficiency. In Jakarta, Indonesia's economic and lifestyle capital, urban customers increasingly demand digital, seamless, and personalized experiences in optical services. According to the World Health Organization (WHO, 2019), there has been a global shift toward interactive and digitally integrated vision care. However, empirical studies in Indonesia on the effectiveness of CRM in the optical sector remain scarce, fragmented, and lack comprehensive methodological synthesis. This study aims to evaluate the effectiveness of digital CRM systems in improving customer satisfaction within Jakarta's optical retail sector using a mixed-method approach that combines bibliometric and meta-analyses. A bibliometric review of 150 articles from Scopus, Web of Science, DOAJ, SINTA, and Google Scholar (2013–2023) was conducted using VOSviewer to map research trends. Subsequently, a meta-analysis of 32 empirical studies was performed using a random-effects model via the Comprehensive Meta-Analysis (CMA) software. The results reveal that digital CRM significantly impacts customer satisfaction (effect size = 0.61, 95% CI, p < 0.01). Among the CRM dimensions, customer tracking systems showed the highest influence (0.68), followed by loyalty programs (0.63) and automated feedback systems (0.59). This study affirms the strategic importance of CRM in the optical industry. It recommends upskilling optical professionals in digital CRM tools and fostering collaboration with local technology developers for service integration. Further primary research in Jakarta is encouraged to refine the CRM models tailored to urban optical practices.